TRANSLATION QUALITY OF GOOGLE TRANSLATE IN THE ARTICLE ENTITLED “VAGINAL BIRTH AFTER CAESAREAN” BY HANNAH DAHLEN - Cahyaningrum, Ika Oktaria; Widiyantari, Yunita (Kajian Linguistik dan Sastra, 2018)
Google is a large company engaged in technology, besides that Goolge also provides software with advanced technology in the field of translation. In this study, we will discuss the quality of translation from Google Translate as one of the online translation engines that are widely used by users. There are several problems that arise in online translation machines, one of which is the aspect of equivalence of words in the target language. This research is a qualitative descriptive study, where the focus of the problem is aimed at analyzing the quality of the translation produced, while the source data is taken from an online English article. Validation of this research data in the form of level of assessment and acceptance was done by questionnaire method by distributing assessment questionnaires to rater, while for readability quality, the researcher used the interview method on the target readers. From the results of the study there were 21 accurate data, and 9 data were less accurate, while 20 data were received and 10 data were not acceptable, for readability 19 the data entered into high readability and 11 data entered into moderate readability. From the results of the study it can be concluded that technological sophistication is a solution to the problem of translation, but on the other hand it cannot be denied that the quality produced by online translation services is also not entirely accurate, acceptable and has high readability.